2014
DOI: 10.1111/1471-0528.12972
|View full text |Cite
|
Sign up to set email alerts
|

Intake of dairy products and calcium and prevalence of depressive symptoms during pregnancy in Japan: a cross‐sectional study

Abstract: Objective To examine the relationship between the intake of dairy products and calcium and the prevalence of depressive symptoms during pregnancy.Design Cross-sectional study. Setting Kyushu Okinawa Maternal and Child Health Study (KOMCHS).Sample A cohort of 1745 pregnant Japanese women.Methods Dietary intake during the preceding month was assessed using a self-administered diet history questionnaire. Scores of 16 or higher on the Center for Epidemiologic Studies Depression Scale denoted depressive symptoms. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
34
5
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 21 publications
7
34
5
4
Order By: Relevance
“…This finding differed from our expectations, based on previous research by Miyake et al (2015), who reported that a higher intake of yogurt was associated with lower prevalence of depressive symptoms during pregnancy. The difference between our results and those reported by Miyake et al (2015) may be attributable to several factors.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This finding differed from our expectations, based on previous research by Miyake et al (2015), who reported that a higher intake of yogurt was associated with lower prevalence of depressive symptoms during pregnancy. The difference between our results and those reported by Miyake et al (2015) may be attributable to several factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Miyake et al (2015) previously reported that a higher intake of yogurt may be associated with a lower prevalence of psychological distress in pregnant women, so here we assessed the effect of yogurt in detail. In particular, it was included as a continuous predictor in a working model, and a linear spline interpolation with one knot was used to represent a nonlinear association between food intake and the prevalence of psychological distress due to food refusal and overeating.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Outro estudo brasileiro, agora com gestantes da capital paulista, encontrou como média de ingestão dietética diá-ria desse micronutriente 633mg 9 . Num trabalho internacional, com 1.745 gestantes japonesas, não considerando o uso de suplementos, a média de ingestão foi inferior à dos trabalhos brasileiros: 502,8mg 10 , revelando que este não é um problema restrito ao Brasil.…”
unclassified